2020
DOI: 10.3390/d12040141
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Urbanization and Fire Disturbance on Plant-floral Visitor Mutualistic Networks

Abstract: The biodiversity loss resulting from rising levels of human impacts on ecosystems has been extensively discussed over the last years. The expansion of urban areas promotes drastic ecological changes, especially through fragmentation of natural areas. Natural grassland remnants surrounded by an urban matrix are more likely to undergo disturbance events. Since grassland ecosystems are closely related to disturbances such as fire and grazing, grassland plant communities, pollinators, and their interaction network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…Based on previous studies which reported that disturbance reduces modularity in plant‐pollinator networks (Beal‐Neves et al., 2020; Pinho et al., 2017), we expected that modularity pattern would differ between the logged and old‐growth forests. On the contrary, there was no difference in modularity structure of liana–tree network between the logged and old‐growth forests.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies which reported that disturbance reduces modularity in plant‐pollinator networks (Beal‐Neves et al., 2020; Pinho et al., 2017), we expected that modularity pattern would differ between the logged and old‐growth forests. On the contrary, there was no difference in modularity structure of liana–tree network between the logged and old‐growth forests.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about interactions of insect pollinators and plant communities in South Brazilian grasslands, but a few studies have indeed showed butterflies, bees, and beetles as abundant and frequent floral visitors in the study region (Pinheiro et al 2008;Oleques et al 2017;Beal-Neves et al 2020). Bee abundance and richness, and butterfly abundance were greatly amplified in freshly-burnt patches, largely attracted by floral resource improvement in these grasslands.…”
Section: Changes In Pollinator Diversitymentioning
confidence: 89%
“…The Park rangers from PNMSH record an accurate burning history of each grassland site, and this was used as a basis to select burned patches used in this study. For the study region (including sites within the PNMSH), Beal-Neves et al, (2020) have shown a positive relationship between time-since-fire (as an indicative of fire frequency) and urbanization (proximity to urban areas), indicating that grassland patches closer to an urban matrix are more likely to burn. There are no historical records of wildfires, i.e., by natural causes, for the study region.…”
Section: Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…Our search resulted in three plant community-level studies in the grasslands of the Pampa domain of Rio Grande do Sul (Pinheiro et al 2008;Oleques et al 2019;Beal-Neves et al 2020). In addition, were found another 23 case pollination studies from grasslands of both phytogeographical domains, including one unpublished manuscript (RS Avila Jr unpubl.…”
Section: Plant-pollinator Interactions Studiesmentioning
confidence: 99%